EFFECT OF MIXED SUPPLEMENTATION OF AMINO ACIDS LYSIN, METHIONINE, AND TRYPTOPHAN IN LOW QUALITY RATION ON PERFORMANCE OF BALI PIGS - I P. M., CANDRADIARTA; SUMADI, I K.; MAHARDIKA, I G. (Majalah Ilmiah Peternakan; Vol 24 No 1 (2021): Vol. 24 No. 1 (2021)DO - 10.24843/MIP.2021.v24.i01.p07, 2021)
The purpose of this study was to determine the effect of lysine, methionine and tryptophan amino acid supple- mentation on low-quality rations on the performance of bali pigs. The material used was 12 bali pigs with an initial weight of 11.41 ± 0.91 kg. The design used was a completely randomized design (CRD) with 3 treatments and 4 replications. Treatment P0 (50% yellow corn + 49% pollard + 0.5% mineral 10 + 0.5% NaCl), P1 (Ration P0 supp- lemented with 0.75% lysine, 0.20% methionine and 0.07% tryptophan of the total rations), P2 (ration 40% yellow corn + 43% pollard + 16% concentrate CP152 + 0.5% mineral 10 + 0.5% NaCl). The variables observed were body weight, weight gain, feed consumption, and feed conversion ratio. The results showed that the supplementation of amino acids lysine, methionine and tryptophan on the performance of bali pigs showed a significantly different effect (P<0.05) on the variables of body weight, weight gain, ration consumption and feed conversion ratio. It can be concluded that the basal ration supplemented with essential amino acids 0.75% lysine, 0.20% methionine and 0.07% tryptophan in bali pork rations can increase body weight, gain weight, consume rations, and feed conversion ratio.